Metazoarios parásitos de Astronotus ocellatus "acarahuazú" colectados del mercado de Belén, Iquitos - Perú 2022 - Souza Alvarado, Carlos Jack (2023)
The main objective of this work was to identify taxonomically the parasiticmetazoans present in Astronotus ocellatus "acarahuazú" from the Mercado de Belén, Iquitos – Peru 2022. The work was carried out through the observation, search, identification of parasites in Astronotus ocellatus. The analysis of the fish was carried out in the Laboratory of Parasitology and Aquatic Health of the Research Institute of the Peruvian Amazon (IIAP). In the study, the genus Posthodiplostomum sp., Contracaecum sp., Sebekia sp., and the monogenean species Gussevia asota, Gussevia astronoti and Gussevia rogersi. Likewise, the calculation of the parasitic indices was carried out, resulting in the species Gussevia asota and Gussevia astronoti having the highest parasitic indices with a prevalence of 100% respectively, intensity of 318 and 230 individuals, intensity and average abundance of 7.95 and 5.75 larvae on average respectively based on the analysis of 40 specimens of Astronotus ocellatus; Regarding the correlation, only a statistically significant correlation was obtained between the size of the Astronotus ocellatus specimens and parasitic abundance. These mentioned data allow us to conclude that the parasitic fauna existing in Astronotusocellatus analyzed in this present study is made up of 1 genus of trematode, 1 genus of nematode, 1 genus of pentastomid and 3 species of monogeneans.